Poor sleep, not getting enough sleep and neuroticism as potential risk factors for anxiety and depression symptoms - Faia, Filipa Isabel Tavares (2023)
Dissertação de Mestrado em Neuropsicologia Clínica: Avaliação e Reabilitação apresentada à Faculdade de Psicologia e de Ciências da Educação